The Effect of Using Array Technique on Semi-Circular Patch Microstrip Antenna with 2.4 GHz Frequency in Supporting Wireless Body Area Network Technology - Baharuddin; Agung Bhaskara; Amirul Luthfi; Rina Angraini; Haniza Yazid (JURNAL NASIONAL TEKNIK ELEKTRO, 2022)
This paper aims to design a semi-circular patch microstrip antenna that can work at a frequency of 2.4 GHz (band 2360 MHz - 2400 MHz) to support Wireless Body Area Network technology (WBAN). One of the devices connected to WBAN technology is a Holter monitor and medical data recorder that forms a medical network for post-operative or monitoring ICU patients (Intensive Care Unit). To support one of the WBAN technologies, an antenna is needed that has considerable gain and bandwidth characteristics. To increase the gain and bandwidth, the array method is used on antennas with inset feed unification. The antenna design was simulated using CST Studio Suite 2019. The use of array methods on microstrip antennas can increase the gain by 132.9%, which is 5.73 dB. The simulation results obtained a return loss of -17.223 dB with a bandwidth of 88.3 MHz in the frequency range of 2357.6 MHz - 2445.9 MHz